Diabetes mellitus and Endothelial Dysfunction - Delgado-Butrón, César (2021)
The Endothelial Dysfunction (ED) in diabetes results from a variety of metabolic factors wich influence the glucotoxicity, lipotoxiciy, insulin resistance and the reciprocal interaction between them. There are a number of functional alterations following to ED, as: active endothelial cell proliferation, abnormalities in vascular flux and permeability, pathologic  angiogenesis,  decrease of the fibrinolysis, vascular occlusion, increase  proinflamatory gene expression and multiple effects dependent on the increment of reactive oxygen species (ROS) and the oxidative stress. These and other poorly understood effects make the ED a key and relevant component in the pathogenesis of diabetic micro and macrovasculopahy. The microvascular complications in retina, glomerulus  and vasa nervorum in the diabetes mellitus implicate an abnormal function of the endothelial cell, characterized by vascular changes, production of growth factors and cytokins, activation of proinflamatory genes, deposition of extracelular matrix and others, wich can be considered  like the first step in the progression of diabetic micrangiopathy. As far as the macrovascular complications, it is important to emphasize that ED precedes atheroesclerosis.